2013
DOI: 10.4103/1793-5482.110274
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect on normal brain tissue during a combinational therapy of 2-deoxy-d-glucose and hypofractionated irradiation in malignant gliomas

Abstract: Purpose:To investigate the effect of 2-deoxy–D-glucose (2-DG), an inhibitor of glucose transport and glycolysis, on glioblastoma and the normal brain tissue during combined treatment with hypofractionated radiotherapy.Materials and Methods:Twenty patients with malignant gliomas (18 Glioblastoma Multiformae, 2 Anasplastic Astrocytoma grade III) following surgery were treated weekly (once) with 2-DG, (250 mg/kg body weight), followed by 5 Gy of radiation to the tumor bed per fraction for 7 weeks. Clinical evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…133,134 Moreover, in phase-I-III clinical trials, negligible normal tissue toxicity, enhanced survival and significant improvement in the quality of life has been observed in cerebral glioma patients following administration of 2-DG with hypofractionated radiotherapy. 40,[133][134][135][136][137] Results from murine studies have shown that the response of the tumors to the combined treatment of 2-DG and irradiation is heterogeneous with complete (cure; tumor-free survival) and partial (growth delay) response, which correlates well with the immune stimulation, switch of Th2 cells to Th1 cells and a significant reduction in Treg numbers in spleen, peripheral blood, lymph node and tumor. 133,134,138 However, significant effects on Treg cells was not observed in the non-tumor bearing mice, suggesting a differential effect of 2-DG on Tregs in normal and tumor-bearing mice.…”
Section: -Deoxy-d-glucose (2-dg)mentioning
confidence: 99%
“…133,134 Moreover, in phase-I-III clinical trials, negligible normal tissue toxicity, enhanced survival and significant improvement in the quality of life has been observed in cerebral glioma patients following administration of 2-DG with hypofractionated radiotherapy. 40,[133][134][135][136][137] Results from murine studies have shown that the response of the tumors to the combined treatment of 2-DG and irradiation is heterogeneous with complete (cure; tumor-free survival) and partial (growth delay) response, which correlates well with the immune stimulation, switch of Th2 cells to Th1 cells and a significant reduction in Treg numbers in spleen, peripheral blood, lymph node and tumor. 133,134,138 However, significant effects on Treg cells was not observed in the non-tumor bearing mice, suggesting a differential effect of 2-DG on Tregs in normal and tumor-bearing mice.…”
Section: -Deoxy-d-glucose (2-dg)mentioning
confidence: 99%
“…At higher doses, dose-limiting side effects occurred in two of six patients [37]. Adapting the recommended treatment schedule in another clinical trial, surgical re-exploration and histological tumor analysis in 13 of 20 patients revealed extensive tumor necrosis with surrounding tissue being well-preserved [38]. …”
Section: Targeting Cancer Metabolismmentioning
confidence: 99%
“…As far as we know, this study is the first investigation about the therapeutic effects of combination therapy using cell cycle synchronisation and 2-DG in mouse tumour models. Until now, several preclinical and clinical studies have been performed to evaluate the efficacy of 2-DG treatment in combination with chemotherapy or radiation therapy in lung cancer, osteosarcoma, and human cerebral glioma [11][12][13][14] . Although, results from those studies lacked consensus, 2-DG showed significant improvement in achieving partial or complete response when used prior to radiotherapy or following chemotherapeutic drugs, such as adriamycin, paclitaxel or etoposide.…”
Section: Discussionmentioning
confidence: 99%